Risks and Effects of the Activities of Organizations Providing Courier Services and Non-Store Retail Trade in Bulgaria - Zhelyzkova, Donka; Grozeva, Desislava; Stoyanov, Mihail (Research Papers, 2020)
This study is provoked by the dynamics in the development of modern economic activities stimulated by the penetration of information and communication technologies into the economy and the personal life of the citizens. On this basis, the main purpose of this research is to summarize, in the light of its theoretical nature, the role and place of courier and non-store retail businesses as elements of the supply chain and, on that basis, examining the state and characteristics of the development of courier and non-store retail companies at national level and to point at the possible risks that accompany the implementation of these business activities. In the course of the study, specific theoretical aspects of courier services and retail trade, that takes place outside traditional brick-and-mortar (physical) locations, have been consistently revealed and, on the basis of empirical information, key trends in their change have been traced. The research ends with an attempt to systematize the main risks that accompany the participants in the non-store retail trade and the provision of its logistic support by the companies operating in the field of postal and courier services.